6: Prenatal Diagnostic of Pierre-Robin Sequence (PRS) Using Ultrasound. (July 2021) - Islam, Raeesa; Anstadt, Erin; Bruce, Madeleine; Pfaff, Miles; Canavan, Timothy; Goldstein, Jesse
Abstract : Purpose: Pierre-Robin Sequence (PRS) is characterized by micrognathia and glossoptosis and can result in upper airway obstruction. Prenatal diagnosis of PRS facilitates delivery team preparation for an airway emergency. Routine 20-week ultrasounds screen facial features and can characterize mandibular morphology and the maxillomandibular relationship. This study aimed to evaluate 20-week fetal ultrasounds to determine if specific facial measurements could predict PRS diagnosis and disease severity. Methods: A retrospective case control study of 40 patients with PRS and 40 gender-matched controls (24 male, 16 female in each cohort) between January 2014 and May 2019 was performed. Respiratory and surgical interventions were recorded and scored for severity. Mid-sagittal profile images of the ultrasounds were reviewed and measured for 3 parameters to assess micrognathia: facial nasomental angle (FNMA), facial-maxillary angle (FMA), and alveolar overjet. FMA <66°and FNMA <136° signify micrognathia. A one-tailed t-test was calculated and the mean ± standard deviation was reported. Results: Patients with PRS demonstrated significantly smaller FNMA compared to the control group (129.6 ± 9 vs.137.9 ± 2.8, respectively; p <.001). FMA was significantly smaller in the PRS group compared to the control group (64.1 ± 9.3 vs. 75.3 ± 6.5; p<.001). The PRS group also demonstrated significantly larger overjet compared to the control group (3.7 ± 1.3 vs. 2.3 ± 0.8, respectively, p<.001). In the PRS group, 53% had an abnormally acute FMA compared to 3% in the control group. For FNMA, 82% in the PRS group demonstrated micrognathia compared to 18% in the control group. In the PRS cases, 38% did not require external respiratory support (n=15), 43% needed supplemental oxygen by nasal cannula or CPAP (n=17), and 20% were intubated (n=8). As respiratory support needs increased, median FMA decreased and alveolar overjet increased. In the control group, 93% required no external respiratory support (n=37) and 7% needed supplemental oxygen by CPAP (n=3). In the PRS cases, 45% received mandibular distraction or tongue-lip adhesion (n=18), 15% underwent supraglottoplasty only (n=6), 8% required tracheostomy (n=3) and 32% did not require surgical intervention (n=13). Surgical patients tended to have smaller FNMAs and greater overjet compared to nonsurgical patients; median FNMA was 127° versus 132°, and median overjet was 2.8 versus 4.15 mm, respectively, however this was not significant. None of the control patients underwent surgical intervention. Conclusions: Mandibular features on 20-week anatomy ultrasound can be measured to predict PRS prenatally and prepare for respiratory intervention at delivery to minimize hypoxia at birth. Alveolar overjet, previously not described in prenatal ultrasound literature but routinely assessed on neonatal clinical evaluation, is measurable and has utility in prenatal diagnosis, as do FMA and FNMA.